An extreme entity in differential diagnosis of musculoskeletal involvement-fibrodysplasia ossificans progressiva: a case based review - Mustafa Çakan; Nuray Aktay-Ayaz; Şerife Gül Karadağ; Gonca Keskindemirci (The Turkish Journal of Pediatrics)
Fibrodysplasia ossificans progressiva is one of the most devastating disorder of mankind characterized by progressive heterotopic ossification. Apart from hallux valgus, other symptoms start to develop in the first decade of life. The initial symptoms are tumefactive lesions on the back that gives an impression of benign or malignant tumoral lesion. It may cause restricted motion of the neck and shoulders and magnetic resonance imaging of the lesions may be reported as myositis or myofasciitis and these children may be referred to rheumatologists. Currently there is no definitive treatment of the disease but the most important issue in these patients is `primum non nocere`, because any invasive procedure could potentially trigger a flare and heterotopic calcification. Herein, we present a young case of fibrodysplasia ossificans progressiva to remind the typical signs and symptoms of the disease to all clinicians caring for children.